Oxford New Syllabus Primary Mathematics 5 - Oh, Brandon; Pearlyn, Gek (Karachi: Oxford university press, 2022)
New Syllabus Primary Mathematics (NSPM) is a comprehensive series of textbooks and workbooks that adopts the Concrete-Pictorial-Abstract approach. The (C-P-A) approach forms an integral part of the learning process. NSPM incorporates the use of concrete aids and manipulatives.. It is specially written to reflect a student-centred approach, which serves to engage pupils so that they have a solid foundation in Mathematics.
The New Syllabus Primary Mathematics series is designed to build a strong mathematical foundation for primary students. The textbooks and workbooks incorporate several key features to facilitate learning: Concrete-Pictorial-Abstract (C-P-A) approach: Concepts are introduced using concrete aids and manipulatives, and then progress to pictorial and abstract representations. Chapter Openers: Start each chapter with familiar events to spark students' curiosity. "Recap": Helps students build on their prior knowledge. "Let's Learn": Introduces new concepts using engaging pictures and manipulatives. "Activity Time": Provides learning experiences through group work, games, and IT-based activities. "Mind Workout": Encourages critical thinking and the application of concepts to non-routine problems. "Maths Journal": Promotes reflection on the learning process.
Keywords: Mathematics - Text Book